Spatial pattern of Quercus ilex and Quercus pubescens recruitment in Pinus halepensis dominated woodlands - Lookingbill, T. R.; Zavala, M. A. (Journal of Vegetation Science, 2000)
Abstract. European Mediterranean landscapes have undergone changes in structure in recent years as a result of widespread agricultural land abandonment and cessation of silvicultural regimes. Studies concerning the regeneration dynamics of dominant forest species have become critical to the prediction of future landscape trends in these changing forest stands. Quercus ilex (holm oak) and Q. pubescens (downy oak) are considered to be the terminal point of secondary succession in extensive areas of the Mediterranean region. Recent studies, however, have suggested the existence of recruitment bottlenecks in oak genet populations as a result of current management regimes. In this study, we present evidence of the successful establishment of Q. ilex and Q. pubescens in Pinus halepensis (Aleppo pine) woodlands. We investigate the distribution patterns and spatial relationships among oak recruits and resident pines. Established P. halepensis is randomly distributed throughout the study area. Oak seedlings are positively associated with pine trees, suggesting that P. halepensis individuals provide safe sites for oak genet recruitment. We show that spatial patterns of recruitment are in agreement with the general model of spatial segregation described for other Mediterranean plant communities, with seeder species colonizing large openings after disturbance, followed by a more aggregated recruitment of resprouter species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: mediterranean forest; Monte Carlo simulation; Nearest neighbour analysis; Nurse effect; Ripley's K-analysis; spatial analysis; succession